Beyond Words : Illness and the Limits of Expression - Conway, Kathlyn (Book collections on Project MUSE., 2013)
The author, a three-time cancer survivor, believes that the triumphalist approach to writing about illness fails to do justice to the shattering experience of disease. By wrestling with the challenge of writing about the reality of serious illness and injury, she argues, writers can offer a truer picture of the complex relationship between body and mind. -- Provided by publisher.